Students’ Perception of Islamic Values Integration in English Language Teaching at an Islamic Junior High School - Indawati; Nur Hidayanto Pancoro Setyo Putro (Universitas Islam Negeri Palopo, 2026)
The integration of Islamic values into English language teaching is relevant in the context of education at Islamic schools. This study aims to examine students’ perceptions of the integration of Islamic values into English language teaching. This study employed a descriptive quantitative design supported by qualitative data. The participants were 20 eighth-grade students at an Islamic junior high school in Sumenep, Madura. Data were collected through a Likert-scale questionnaire and open-ended questions as supporting data. Quantitative data were analyzed using percentage distribution and mean scores, while the qualitative data were analyzed using simple descriptive method to support the quantitative results. The results of the study indicate that most students have a positive perception of the integration of Islamic values into English language learning. students’ perceptions of the integration of Islamic values were categorized as high, with a mean score of 4.04. Similarly, students’ interest in learning English was also categorized as high, with a mean score of 4.02. The distribution of responses indicates that most students selected